The Neuropsychological Basis of Lexically-based Language Teaching - Kweldju, Siusana (TEFLIN Journal, 2004)
This paper proposes a lexically-based approach for the teaching of English in Indonesia. To develop the approach, neurolinguistic and psycholinguistic research findings for L2 learning are re-viewed because this approach has to consider how human mind stores, processes, recognizes and retrieves words. Neurobiologically, the learning of L 1 is different from L2. Thus, the lexically-based approach gives more emphasis on chunking, the learning of formulaic phrases, and conscious awareness of learning.